Fish biodiversity survey (2009) of streams in the Ayer Hitam Forest Reserve, Puchong, Selangor - Lirong, Yu Abit; Kamaruddin, Izharuddin Shah; Zakaria, Mohd Rozhan; Mohd Yasin, Ina Salwany; Abd. Satar, Mustafa Kamal (Universiti Putra Malaysia Press, 2012)
A study was carried out to determine the different fish species inhabiting the streams of Ayer Hitam ForestReserve (AHFR) in Puchong, Selangor. The study was carried for a period of days (from 13 to 16 April 2009)during the Scientific Expedition of AHFR, Puchong, organized by the Faculty of Forestry, Universiti PutraMalaysia (UPM). The samples were collected using a variety of methods at three stations that were designatedas Station A, Station B and Station C within the AHFR riverine system. These samples were then preserved in90% ethanol solution and sent to the laboratory for identification. From the sampling, eleven indigenous fishspecies (namely, Puntius binotatus, Luciocephalus pulcher, Clupeithys sp., Rasbora einthoveni, Hemiramphodonpogognathus, Rasbora heteromorpha, Sphaerichtys osphronemoides, Rasbora sumatrana, Beta pugnax,Glossogobous giuris and Clarias macrocephalus) were identified to inhabit the AHFR riverine system.